Novel Variation and Evolution of AvrPiz-t of Magnaporthe oryzae in Field Isolates - Qun Wang; Jinbin Li; Lin Lu; Chengxing He; Chengyun Li (Frontiers in Genetics, 2020)
The product of the avirulence (Avr) gene of Magnaporthe oryzae can be detected by the product of the corresponding resistance (R) gene of rice and activates immunity to rice mediated by the R gene. The high degree of variability of M. oryzae isolates in pathogenicity makes the control of rice blast difficult. That resistance of the R gene in rice has been lost has been ascribed to the instability of the Avr gene in M. oryzae. Further study on the variation of the Avr genes in M. oryze field isolates may yield valuable information on the durable and effective deployment of R genes in rice production areas. AvrPiz-t and Piz-t are a pair of valuable genes in the Rice-Magnaporthe pathosystem. AvrPiz-t is detectable by Piz-t and determines the effectiveness of Piz-t. To effectively deploy the R gene Piz-t, the distribution, variation, and evolution of the corresponding Avr gene AvrPiz-t were found among 312 M. oryzae isolates collected from Yunnan rice production areas of China. PCR amplification and pathogenicity assays of AvrPiz-t showed that 202 isolates (64.7%) held AvrPiz-t alleles and were avirulent to IRBLzt-T (holding Piz-t). There were 42.3–83.3% avirulent isolates containing AvrPiz-t among seven regions in Yunnan Province. Meanwhile, 11 haplotypes of AvrPiz-t encoding three novel AvrPiz-t variants were identified among 100 isolates. A 198 bps insertion homologous to solo-LTR of the retrotransposon inago2 in the promoter region of AvrPiz-t in one isolate and a frameshift mutation of CDS in another isolate were identified among 100 isolates, and those two isolates had evolved to virulent from avirulent. Synonymous mutation and non-AUG-initiated N-terminal extensions keeps the AvrPiz-t gene avirulence function in M. oryzae field isolates in Yunnan. A haplotype network showed that H3 was an ancestral haplotype. Structure variance for absence (28.2%) or partial fragment loss (71.8%) of AvrPiz-t was found among 39 virulent isolates and may cause the AvrPiz-t avirulence function to be lost. Overall, AvrPiz-t evolved to virulent from avirulent forms via point mutation, retrotransposon, shift mutation, and structure variance under field conditions.